Cross-cultural adaptation of the consensus auditory-perceptual evaluation of voice (cape-v) into Malay: validity and reliability study - Mossadeq, Nurhayati Mohd (2023)
Auditory-perceptual rating of voice is one of the compulsory clinical voice evaluations. One tool that has gained attention for this purpose is the Consensus Auditory-Perceptual Evaluation of Voice (CAPE-V). The CAPE-V has been reported to have a more standardized approach in evaluating the voice. Because of its advantages, the CAPE-V has been adapted in several languages to suit specific populations. Accordingly, the adaptation of the CAPE-V into Malay is essential for its utility among the Malaysian population, which this study aims to achieve. This crosssectional study involves translating the CAPE-V into Malay, followed by establishing the validity and reliability of the translated CAPE-V. The translation processes (i.e., forward and backward) involved 4 translators with at least 14 years of experience. Most items were similarly translated by the translators, except for a few, which were subsequently accepted as similar, following consensus among the translators. The content validity analysis involved 2 raters, with at least 12 years of clinical experience, using the CVI method. The CVI value was above the acceptable level, thus, all items were retained. For the analyses of construct validity, concurrent validity, inter-rater reliability, and intra-rater reliability, the translated CAPE-V, termed the Malay CAPEV, was used to rate the voice samples recorded from 38 participants, which consisted of 19 individuals with normal voices (6 males and 13 females) and 19 individuals with voice disorders (8 males and 11 females). The ratings were performed by 3 raters with at least 12 years of clinical experience. The construct validity was examined by using the known-group method involving a comparison of the scores of each vocal parameter of the Malay CAPE-V of the normal and disordered voice groups using the Mann- Whitney U test, which indicated a statistically significant difference between the two groups. For the concurrent validity, the relationship between the scores of each vocal parameter of the Malay CAPE-V and GRBAS Scale were examined using the Spearman correlation, which indicated a statistically significant very strong positive correlation between the two tools. For the inter-rater reliability and intra-rater reliability, the ICC values of the scores of each vocal parameter of the Malay CAPEV were all above the acceptable level. Therefore, the Malay CAPE-V is a valid and reliable tool for an auditory-perceptual rating of voice among the Malaysian population.